Variable gravity effects on thermal instability of nanofluid in anisotropic porous medium - Chand, Ramesh; Rana, G.C.; Kumar, S. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we study the effects of variable gravity on thermal instability in a horizontal layer of a nanofluid in an anisotropic porous medium. Darcy model been used for the porous medium. Also, it incorporates the effect of Brownian motion along with thermophoresis. The normal mode technique is used to find the confinement between two free boundaries. The expression of the Rayleigh number has been derived, and the effects of variable gravity and anisotropic parameters on the Rayleigh number have been presented graphically.
Keywords: nanofluid; anisotropic porous medium; Rayleigh number; variable gravity